2020
DOI: 10.1111/jcmm.15984
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic alternations of microRNAs and DNA methylation contribute to gestational diabetes mellitus

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 51 publications
(102 reference statements)
0
18
0
Order By: Relevance
“…MicroRNAs (miRNAs) are factors that regulate biological functions and participate in biological processes such as cell division, proliferation, differentiation, and development. Recent studies have shown that miRNAs are also involved in the regulation of adipocyte differentiation, glucose and lipid metabolism, energy homeostasis, and insulin production and secretion, suggesting that such small nucleic acid molecules may be involved in the pathogenesis of metabolic diseases such as obesity and diabetes [ 20 ]. The expression of miRNA-143 in the placenta tissue of patients with gestational diabetes increased, suggesting that miRNA-143 may be related to the pathogenesis of patients with gestational diabetes and that exercise can reduce the expression of miRNA-143 in patients with gestational diabetes and help reduce blood sugar in patients with gestational diabetes [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs (miRNAs) are factors that regulate biological functions and participate in biological processes such as cell division, proliferation, differentiation, and development. Recent studies have shown that miRNAs are also involved in the regulation of adipocyte differentiation, glucose and lipid metabolism, energy homeostasis, and insulin production and secretion, suggesting that such small nucleic acid molecules may be involved in the pathogenesis of metabolic diseases such as obesity and diabetes [ 20 ]. The expression of miRNA-143 in the placenta tissue of patients with gestational diabetes increased, suggesting that miRNA-143 may be related to the pathogenesis of patients with gestational diabetes and that exercise can reduce the expression of miRNA-143 in patients with gestational diabetes and help reduce blood sugar in patients with gestational diabetes [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The insulin was administered via subcutaneous injection, which ensures the effectiveness of the drug as well as potency duration. Notably, in terms of pregnancy outcome and neonatal complications, the combined therapy also outperformed the monotherapy because the reason can be that insulin aspart plus exercise therapy improves the patient's systemic blood circulation, reduces insulin resistance, controls the body's blood sugar, and minimizes the impact on pregnant women and fetuses, thus reducing the incidence of complications during pregnancy [ 20 ]. It further indicates that the combination therapy benefits the control of gestational diabetes mellitus and contributes to a lower incidence of pediatric complications.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, SAM must be constantly produced to maintain SAM-to-SAH ratios sufficient to support methyltransferase activity ( Clarke, 2006 ; Krijt et al, 2009 ; Walsh et al, 2018 ). Too much or too little methylation of substrates by SAM has been associated with cancer, diabetes, along with other diseases ( Gharipour et al, 2020 ; McMahon et al, 2017 ; Zhu et al, 2020 ). Therefore, intracellular SAM levels are tightly controlled to maintain homeostasis, with loss of regulation resulting in cellular dysfunction ( Gao et al, 2019 ; Lio and Huang, 2020 ; Ouyang et al, 2020 ; Parkhitko et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The matrix files of the above three data sets were downloaded and the R language limma package was utilized to screen out deferentially expressed genes (DEGs), miRNAs (DEMs), and methylated CpG probes (DMPs) (W. Zhu W. et al, 2020 ). Subsequently, DEGs, DEMs, and DMPs were filtered out, using p <0.05 and abs (t) > 2 as cutoff values.…”
Section: Methodsmentioning
confidence: 99%